The role of Intellectual Property Rights in Enhancing Regional Development - Sein, Yee Yee; Prokop, Viktor (Academic Conferences International Limited, 2022)
Intellectual property rights (IPRs) are recognized as a growth enhancing factor for the economy. IPRs can influence the growth process through the domestic and external sectors of an economy. Therefore, researchers are increasingly interested in the role of IPR protection in the economic growth of countries. In OECD countries, most industries rely on innovation with innovative technology, hence, the role of IPR is important in stimulating the diffusion of knowledge to foster innovation that contributes to the regional development. Based on the above-mentioned, the research aims to analyze the role of IPR protection in enhancing regional development in OECD countries. The study uses the latest data set from the OECD and World Bank. We found that IPRs have a positive and significant effect on regional economic growth in OECD countries. FDI is also highly significant effect on regional economic growth. The result of this study provides interesting results that will support policy makers in considering improving intellectual property rights of inventors when formulating policies for national and regional development.
Role práv duševního vlastnictví při posilování regionálního rozvoje
Keywords: intellectual property rights (IPRs); patents; regional development; economic growth; FDI; práva duševního vlastnictví (IPR); patenty; hospodářský růst; přímé zahraniční investice; regionální rozvoj